Advances in Nanotoxicology: Health and Safety - Natalia Krasteva; Milena Georgieva (Nanomaterials, 2026)
The rapid development of nanotechnology has resulted in the widespread incorporation of engineered nanomaterials into biomedical, industrial, and consumer applications, including drug delivery systems, imaging agents, therapeutic platforms, cosmetics, food packaging, and biosensing technologies [...]